Exploring Anthropometric, Biochemistry and Nutritional Attributes in Overweight and Obese Women: Insights from the Serbian Cohort - Petrović, Anka (Journal of Medical Biochemistry, 2024)
Summary: Introduction: Anthropometric measurements (AMs), such as waist circumference and body mass index (BMI), are dominant indicators of overweight and obesity. Nevertheless, other AMs, such as waist‒hip ratio, waist circumference and indices of visceral adiposity index (VAI), body mass fat index (BMFI), cardiometabolic index (CMI) and waist‒to‒height ratio (WtHR) have been shown to be more significant and discriminatory than BMI in predicting cardiometabolic risk. Methods: The aim of this study was to comprehensively investigate the anthropometric, biochemical and nutritional characteristics a sample of overweight and obese women in Serbia, focusing on potential differences related to AM and its association with specific biochemical markers.Results: The final analytical sample consisted of 57 females (average age 37.16 ± 7.27 years, range: 21–55 years). A strong positive correlation was observed between triglycerides (TG) and both the VAI (r = 0.896, p < 0.001) and the CMI (r = 0.896, p < 0.001), both with high statistical significance. Conversely, a strong negative correlation was found between high-density lipoprotein cholesterol (HDLc) and both VAI (r = −0.601, p < 0.001) and CMI (r = −0.566, p < 0.001). Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were significantly positively correlated with both WtHR and BMFI: SBP and WtHR (r = 0.343, p = 0.009), SBP and BMFI (r = 0.310, p = 0.019), DBP and WtHR (r = 0.368, p = 0.005), and DBP and BMFI (r = 0.377, p = 0.004). The analysis of biochemical parameters indicated no significant differences between groups, except for TG levels, which were significantly higher in the obese group (p = 0.045).Conclusion: Although the AMs of the subjects were significantly different, energy intake and macronutrient intake were not significantly different. We did not find significant differences in the intake of most vitamins or minerals between the groups. Additionally, there is inadequate intake of essential nutrients such as vitamin D, iron and selenium, which are critical for overall health. Both groups did not meet the recommended folate intake, which may increase the risk of fetal neural tube defects.
Keywords: anthropometric measurements; BMI; Castelli’s risk ratio; obesity; VAI